Fostering the social and physical challenges of female recreational or professional athletes in pregnancy and postpartum - Rita Santos-Rocha; Anna Szumilewicz (BMC, 2024)
Abstract Combining pregnancy and parenthood with sporting activities or a professional athletic career can be challenging. The objective of this Collection is to gain a deeper understanding of the effects of pregnancy and postpartum on female athletes, both recreational and professional, in order to improve their health and fitness outcomes and support their continued success in sports.